2002
DOI: 10.1287/mksc.21.1.32.155
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Credit on Spending Decisions: The Role of the Credit Limit and Credibility

Abstract: The objective of the present research is to study consumer decisions to utilize a line of credit. The life-cycle hypothesis from economics argues that consumers should intertemporally reallocate their incomes over their life stream to maximize lifetime utility. One form of intertemporal allocation is to use past income (in the form of savings) in the future. A second form is the use of future income in the present. This can only be done if consumers have access to a temporary pool of money that they can draw f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
168
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(180 citation statements)
references
References 22 publications
8
168
1
3
Order By: Relevance
“…In study 3, participants in the credit card (cash) condition responded faster to benefits (costs) than to costs (benefits). This differential focus led credit card primed consumers to express higher reservation prices (studies 1-3) and also affected their product choices (study 4) relative to those primed with cash.T he use of a credit card as a payment mechanism increases the propensity to spend as compared to cash in otherwise identical purchase situations (Feinberg 1986;Hirschman 1979;Prelec and Simester 2001;Soman 2001;Soman and Cheema 2002), a finding typically referred to as the credit card premium. While prior research has explained the spending effects of different payment mechanisms by attributing them to memory processes (Soman 2001), decoupling of purchase from the pain of payment (Prelec and Loewenstein 1998), classical conditioning (Feinberg 1986), and processing fluency (Mishra, Mishra, and Nayakankuppam 2006), they remain silent as to consumers' product evaluations and choices.…”
mentioning
confidence: 99%
“…In study 3, participants in the credit card (cash) condition responded faster to benefits (costs) than to costs (benefits). This differential focus led credit card primed consumers to express higher reservation prices (studies 1-3) and also affected their product choices (study 4) relative to those primed with cash.T he use of a credit card as a payment mechanism increases the propensity to spend as compared to cash in otherwise identical purchase situations (Feinberg 1986;Hirschman 1979;Prelec and Simester 2001;Soman 2001;Soman and Cheema 2002), a finding typically referred to as the credit card premium. While prior research has explained the spending effects of different payment mechanisms by attributing them to memory processes (Soman 2001), decoupling of purchase from the pain of payment (Prelec and Loewenstein 1998), classical conditioning (Feinberg 1986), and processing fluency (Mishra, Mishra, and Nayakankuppam 2006), they remain silent as to consumers' product evaluations and choices.…”
mentioning
confidence: 99%
“…Consequently, individuals that use some sort of credit for payment may consume more. The question arises as to whether this will lead to greater consumption, which in turn causes them to become delinquent (Prelec & Lowenstein, 1998;Soman & Lam, 2002;Soman & Cheema, 2002;Kirchler et al, 2008;Raghubir & Srivastava, 2008;Ponchio, 2006).…”
Section: Preference For Creditmentioning
confidence: 99%
“…Soman and Cheema [22] made several experiments about the effect of credit on a spending decision and they found that a higher credit limit on credit card spending increases spending especially for some groups of users (younger consumers and less educated consumers). The study of credit card debt among college students showed interesting results [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The objective of the paper is to study the impact of the credit card limit on the long-term budget available for spending with the usage of the system dynamics approach, with the presumption that a higher credit limit on credit card spending will decrease the long-term budget available for spending [18,22]. To test this presumption, we used a system dynamics model of the credit card impact on the budget available for spending, which is developed by Ratha [20] as part of the Road Maps program.…”
Section: Introductionmentioning
confidence: 99%